2012
DOI: 10.2174/1874920801205010009
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Physical Self-Concept in Physical Education: Differences by Gender

Abstract: This paper examines the relationship between dispositional goal orientations, the perception of different motivational climates and physical self-concept in physical education classes. An additional purpose was to examine the nature of these relationships among boys and girls. Eight hundred and eighty-four students from a large Spanish metropolitan school district were participants in this study and completed questionnaires assessing the above mentioned variables. Results revealed that sport competence and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
(50 reference statements)
1
8
0
2
Order By: Relevance
“…In addition, the significant differences between male and female participants were found in the seven subscales including coordination, physically active, sport competence, appearance, strength, flexibility, and endurance. This is in line with the findings of previous studies conducted by (Arazi & Hosseini, 2013;Hagger et al, 2005;Moreno-Murcia et al, 2012) who found that male participants tended to have higher physical self-concept than female participants. Arazi & Hosseini (2013) found that male students gained higher significant level of the health; coordination; physical activity; body fat; global physical; competence; sports; global physical self-concept and global esteem scales, while (Hagger et al, 2005)found that boys' scores on all subscales were significantly higher than girls.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, the significant differences between male and female participants were found in the seven subscales including coordination, physically active, sport competence, appearance, strength, flexibility, and endurance. This is in line with the findings of previous studies conducted by (Arazi & Hosseini, 2013;Hagger et al, 2005;Moreno-Murcia et al, 2012) who found that male participants tended to have higher physical self-concept than female participants. Arazi & Hosseini (2013) found that male students gained higher significant level of the health; coordination; physical activity; body fat; global physical; competence; sports; global physical self-concept and global esteem scales, while (Hagger et al, 2005)found that boys' scores on all subscales were significantly higher than girls.…”
Section: Resultssupporting
confidence: 93%
“…Since self-concept scales tend to tap constructs qualities that are typically viewed as "masculine" characteristics,such as assertiveness andconfidence, boysare to be expected to report higher levels of physical self-concept (Hagger et al, 2005). Furthermore, the physical self-concept level was associated with the goal orientation and how the participants perceived the class environment, such as the expectations created by teachers and group pressures, which could affect the image that boys and girls have (Moreno-Murcia et al, 2012). It made female participants underestimate their physical competence (Moreno-Murcia et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the previous work supported link between the perception of a task-involving climate and physical self-concept (Newton et. al, 2004, Moreno-Murcia et al, 2012, it was hypothesized that performance approach and avoidance climates in PE lesson had negative impact on students' different dimensions of self-perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…Her madde 1 (Hiçbir zaman böyle davranmam) ile 5 (Her zaman böyle davranırım) arasında değişen beşli değerlendirme basamağına sahiptir. Geliştirilen 24 maddelik ölçüm aracına ilişkin yapılan yapı analizi sonuçlarına göre, envanterin toplam varyansın % 42 26…”
unclassified